Analyzing the green field investment in Malaysia from 1970 to 2009: A bound testing approach - Mahmoud Khalid Almsafir A.P.; Abdul Latif N.W.B.; Bekhet H.A. (2023)
This paper investigates and estimates the factors influencing Foreign Direct Investment (FDI) in Malaysia. Specifically, the objective of this study is to explore empirically the extent to which the local characteristics of Malaysian economy as determinants of FDI inflows to Malaysia. The Autoregressive Distributed Lag (ARDL) model was employed to explore the short run and long run relationships between FDI and its key determinants for Malaysia by using time series data covering the 1970-2009 period. To achieve this objective, the study employs the Johansen co-integration and Error-Correction Model (ECM). The paper focuses on the factors influencing FDI in Malaysian economy. Both the economics theory and prior research work suggests that FDI can be expected to enhance economic growth. Throughout the study, it was found that there was a co-integration relation between FDI and its determinants in Malaysia. The result of this study shows that FDI plays an important role in the capital formation and hence, the development of the economy.